PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI ARTICULATE STORYLINE PADA MATERI RADIASI BENDA HITAM KELAS XII SMA - Toto Asnawi; Mitri Irianti; Syahril Syahril (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract:Improving cognitive learning outcomes and overcoming the difficulties of class XII high school students in understanding abstract physics lessons such as black body radiation, the effort that researchers can do is to develop learning media using the articulate storyline application. The purpose of this study is to produce learning media using the articulate storyline application on valid material for black body radiation for class XII SMA. This study uses the Research and Development method with the ADDIE development model whose implementation is only up to the development stage. The data obtained from this study is data that has been given by the validator to the learning media that has been developed using a validation assessment sheet. The validation assessment sheet consists of an assessment sheet for learning media and an assessment sheet for learning materials. The learning media assessment sheet consists of 3 assessment aspects, namely display design aspects, video aspects, and aspects of the ease of use of learning media. The learning material assessment sheet consists of 3 assessment aspects, namely the material suitability aspect, the language suitability aspect, and the experimental aspect. The results of this study indicate that the average value obtained from the validation results of learning media development using the articulate storyline application on black body radiation material is 3.45 so that the development of learning media using the articulate storyline application on black body radiation material is declared valid.Key words: Articulate Storyline, Learning Media, Black Body Radiation.